IN VITRO GROWTH INHIBITORY EFFECT OF ZnO NANOPARTICLES ON HUMAN LIVER CANCER CELL LINES (Huh7) - ANANTHALAKSHMI R; XAVIER RAJARATHINAM SR; Mohamed Sadiq A; MOHAMED SADIQ A (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to access the anticancer activity of the biosynthesized ZnO nanoparticles against Huh7 liver cancer cell lines. Methods: The study was carried in vitro using Huh7 cell lines. The ZnO nanoparticles (ZnO NPs) were synthesized using Luffa acutangula peel extract and subjected to characterization by X-ray powder diffraction and transmission electron microscopy. The Huh7 cell lines were treated with ZnO NPs and done 3-(4, 5-dimethylthiazol- 2-yl)-2, 5-diphenyltetrazolium bromide assay. For live and dead assay, the cell lines treated with ZnO NPs were subjected to acridine orange/ethidium (AO/ET) bromide assay. Results: The ZnO NPs synthesized show spherical structure with 10–20 nm size. The 50% of Huh7 proliferation were inhibited at the concentration (IC50) of 40 μg/ml. The AO/ET assay shows compact nucleus and fine cytoplasmic morphology in control cells and apoptotic stage in treated cells Conclusion: This study suggests that ZnO NPs can be prepared in environment-friendly method using aqueous extract of L. acutangula and can be used in cancer treatment effectively.